Revision of different implementations for digital preservation: towards a methodological proposal for preserving and auditing IR reliability - De Giusti, Marisa Raquel (2018)
This work introduces the initial experience of an infrastructure for digital documents preservation in archives or repositories. Prior backgrounds of similar infrastructures are recognized in this work, and among them three successful experiences are described. These experiences are all aimed to connect a digital repository with different software tools able to ensure digital preservation of repository contents according to OAIS ISO 14721 standard (2012). After the description of the three models, we describe a prototype under development in the repositories supported by PREBI-SEDICI (UNLP), which uses the software tools DSpace, Archivematica and ArchivesSpace. In this prototype, DSpace handles the ingest and delivery of digital contents, while Archivematica performs all the required digital preservation activities. This is achieved through a set of microservices applied to a conceptual structure similar to the information package (IP) in its different versions (SIP, AIP, DIP). The resulting structure of the IP includes checksums, original files, logs, transfer documentation and XML metadata. The main purpose of this work is to show the background activities already carried out in institutions around the world, and to start a research project aiming to generate ideas and thoughts in the Latin American context.